The Relationship Between Home Environmental Conditions and Knowledge about Dengue Fever and the Presence of Aedes Sp. Larvae - Maria Sarlina Darumba; Irwan Budiana; Dewi Nur Sukma Purqoti; Mega Rahmawati Sucipto (Journal of Tropical Diseases and Health Science, 2024)
Dengue Hemorrhagic Fever (DHF) is an acute febrile disease caused by the dengue virus, which enters the human bloodstream through the bite of mosquitoes of the genus Aedes, Aedes aegypti or Aedes albopictus. The purpose of this study was to determine the relationship between home environmental conditions and knowledge about dengue hemorrhagic fever with the presence of Aedes sp larvae. In this study, researchers used an analytical research type that aims to determine the relationship between independent variables and dependent variables. This research design is a cross-sectional study where independent variables and dependent variables are studied simultaneously. The research variables are environmental conditions which include the type of landfill, location of the landfill, condition of the landfill, number of landfills, lighting, ventilation, respondent knowledge and the presence of Aedes sp larvae. The method used to observe the presence of larvae in containers was visual inspection. The population in this study was all houses in RT 18, Oesapa Village, including those with dengue fever cases (6 cases) in 2022 and those without. The sample size was the total number of houses in RT 18, which is 42. Respondents were housewives or family members responsible for housekeeping. Data analysis used a chi-square test with a significance level of p>0.05 (95% confidence interval). The results of this study indicate that factors associated with the presence of larvae include the type of landfill (p = 0.000), the number of landfills (p = 0.005), and ventilation (p = 0.000). Other variables examined that were not related to the presence of larvae included the location of the landfill, its condition, lighting, and respondents' knowledge. Community efforts to control larvae include installing wire mesh over each ventilation hole and regularly emptying the landfill at least once a week.